Human-geographical features of transport accessibility research of pre-school and secondary education institutions in the cities of Kharkiv and Warsaw - Kateryna Kravchenko; Yevhen Shpak; Yevhen Khabusev (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2024)
An efficient transport system is one of the important elements of an economically developed city. The quality of transport infrastructure and the provision of logistics services primarily contribute to the accessibility or ease with which people can reach their main destinations, such as work, health care and education, using a particular mode of transport, or a combination of these. In the article, a socio-geographical analysis of transport accessibility of preschool and general educational institutions in Kharkiv and Warsaw was carried out. Features of the methodology of transport accessibility research using geoinformation systems QGIS 3.16 and ArcGis 10.7 are presented based on OpenStreetMap data. On the basis of a spatial GIS analysis of the placement of preschool and secondary education institutions, buffer zones were built, which cover the territory in a 500-meter (approximately 5-minute) accessibility zone.